The Human Gut Virome in Hypertension - Han, Maozhen; Yang, Pengshuo; Zhong, Chaofang; Ning, Kang (Frontiers in Microbiology, 2018)
Abstract Objectives Previous studies have reported that the gut microbiome has an important link with the development of hypertension. Though previous researches have focused on the links of gut bacteria with hypertension, little has been known about the linkage of gut viruses to hypertension and the development of hypertension, largely due to the lack of data mining tools for such investigation. In this work, we have analyzed 196 faecal metagenomic data related to hypertension to aiming to profile the gut virome and linking the gut virome to pre-hypertension and hypertension. Design Here we have applied a statistically sound method for mining of gut virome data and linking gut virome to hypertension. We characterized the viral composition and bacterial composition of 196 samples, identified the viral-type of each sample and linked gut virome to hypertension. Results We stratified these 196 faecal samples into two viral-types and selected 32 viruses as the biomarkers for these groups. We found that viruses could have a superior resolution and discrimination power than bacteria for differentiation of healthy samples and pre-hypertension samples, as well as hypertension samples. Moreover, as to the co-occurrence networks linking viruses and bacteria, we found increasingly pervasive virus-bacteria linkages from healthy people to pre-hypertension people to hypertension patients. Conclusion Overall, our results have shown ample indications of the link between human gut virome and hypertension, and could help provide microbial solutions towards early diagnoses of hypertension.